The Mental Health of Breastfeeding Mothers during COVID-19 Pandemic - Nur Intan Kusuma; Fanny Sukmasary (Asosiasi Pendidikan Kebidanan Indonesia (AIPKIND), 2023)
Background: The current widespread COVID-19 outbreak has been linked to psychological distress and increased mental health symptoms including depression, anxiety, and posttraumatic stress disorder diagnoses in during the postpartum period. The psychological distress in mothers during the postpartum period can have negative consequences for both the mother and the baby. One of negative effect could be an obstacle to optimal breastfeeding. Purpose: This scoping review aims to provide the generate overview and present the results of previous studies related to the mental health of breastfeeding mothers during the COVID-19 pandemic. Methods: This study was carried out using a scoping review approach in accordance with the Arksey and O'Malley’s framework. The search strategy used the keywords that related to the PEOS framework. Databases included PubMed, Wiley Online Library, ScienceDirect, and Embase. The authors also appraised the article's quality by critical appraisal tool. Results: The most of the research was conducted in developed countries (75%). The method of that articles used quantitative method of 17 articles (85%), qualitative method 2 articles (10%) and mixed method 1 article (5%). Based on an analysis of 20 articles, three themes were obtained, namely mental health issues in breastfeeding mothers, factors affecting mental health during COVID-19, the impact of poor mental health in breastfeeding mothers. Conclusion: The Global outbreaks or pandemics have an impact including in breastfeeding mothers. Breastfeeding mothers feel that during the COVID-19 they are experiencing psychosocial problems due to internal and external factors that can influence the mother's decision to provide exclusive breastfeeding.